Epilepsi dan Kehamilan - Riki Sukiandra (Jurnal Ilmu Kedokteran, 2014)
Epilepsy is a chronic neurologic disorder that may complicate pregnancy, about 25%-33,3% epileptic seizures increasedin pregnancies. The main concern in pregnancies complicated by epilepsy includes the increased risk of congenitalabnormalities associated with antiepileptic drugs. Hormones can have major effect on seizure disorders. Women withepilepsy will have changes in seizure patterns when hormones levels shift, such as during pregnancy or right afterpregnancy. A woman with seizure disorder must be managed effectively to minimize the risk of a seizure that couldharm the fetus. Seizures can harm the developing fetus by reducing the blood supply to the placenta. Anti-convulsantmedications should not be discontinued during pregnancy. medications may be switched to those that are known to bethe safest to the developing fetus. This will reduce the risk for neural tube defects like spina bifida. Multiple drugtherapy should be avoided – if possible– and drugs should be given in divided doses to avoid high peak levels. We canprovide women with epilepsy with the available information, advise on the best treatment prior to pregnancy, andwarnings that most AEDs carry a risk above that of untreated epilepsy. Treatment should be planned in womenanticipating pregnancy